The Impact of Teachers' Personalities and Parents' Factors on Senior Secondary School Computer Science Students' Performance (British Journal of Multidisciplinary and Advanced Studies, 2023)
As secondary education institutions try to educate students about the demands of a rapidly changing digital world, it is crucial to understand the factors that influence students' progress in computer science. Students' success in the study of computer science is influenced by a variety of factors outside of the curriculum and instructional methods. Two significant elements that have drawn attention in the education sector are the personalities of teachers and parental involvement. These factors play a significant role in how children learn, act, and succeed academically as a whole. To determine the effects of teachers' personalities and parental influences on senior secondary school computer science students' performance, this study was designed. The research employed a mixed-methods strategy that includes both quantitative surveys and qualitative interviews to collect information from a representative sample of the targeted demographic. A total of 150 respondents, including 100 students and 50 teachers, were chosen at random from five senior secondary schools to make up the study's sample. Four research questions and two research hypotheses served as the study's guiding principles. Data were gathered using a self-structured questionnaire the researcher constructed based on perceptions of students and teachers that examined how parents and teachers might influence students' academic progress in computer science. The four (4) research questions that were posed for the study were evaluated using descriptive statistical methods such as mean and standard deviation, whereas the two study hypotheses were evaluated using the Pearson Product Moment Correlation (PPMC) index coefficient using SPSS Version 23 at the 0.05 level of significance. The results of this study showed that factors such as teachers' academic backgrounds, personalities, and parents' socioeconomic level have an impact on students' academic success in computer science. The study's findings also indicated a correlation between parents' socioeconomic level and their children's academic success and between the qualifications of teachers and students' academic success. As a result, it was recommended among other things, that teachers be encouraged to pursue higher education because doing so will have a significant impact on how they instruct their students.